Multi-Index Layout Optimization of the Thruster System for an Underwater Welding Vehicle - Haihua Zhang; En Yang; Shan Wang; Liangliang Lu; Shifeng Ding (Journal of Marine Science and Engineering, 2026)
Thruster configuration dictates the hydrodynamic stability of underwater welding vehicles, yet standard design protocols rarely penalize undesired forces and moments that compromise precision. This study proposes a multi-index performance evaluation framework that integrates propulsion capability and disturbance minimization into a unified metric. Key indices include the Propulsion Index (PI), Balance Improvement Index (BI), and a final Comprehensive Performance Index (CPI) for multi-scenario ranking. Through CFD-based simulations, a three-stage optimization is conducted, comparing layout schemes, installation angles (30°/45°/60°), and arm lengths (0.75×/1.0×/1.5×). Results show that Layout I achieves a CPI of 0.8592, which is 1.28% higher than that of Layout II. The 45° installation-angle scheme obtains the highest CPI of 0.8592, corresponding to improvements of 14.15% and 16.31% over the 30° and 60° schemes, respectively. For the arm-length optimization, the original arm length also achieves the highest CPI of 0.8592, outperforming the 0.75× and 1.5× arm-length schemes by 6.96% and 2.52%, respectively. These results confirm that the symmetric Layout I with 45° inclined thrusters and the original arm length provides the best overall compromise between task-direction propulsion and hydrodynamic disturbance suppression.